Penyelesaian Sengketa Pegadaian Terhadap Konsumen Atas Rusaknya Objek Jaminan Gadai - Anastasya Mottoh, Kiscya; Lieke Lontoh, Rietha; Benedicta Tambajong, Helena (UNES Law Review, 2023)
PT. Pegadaian in Indonesia are regulated in Law Number 21 of 2011 concerning the Financial Services Authority and regulated in the Civil Code. Looking at the problem of damaged consumer pawn objects due to PT. Pegadaian, four-wheeled vehicles are often the object of pawn collateral for loan funds. The debt and receivable agreement and the additional guarantees are not free from errors on the part of one of the parties, such negligence is a breach of contract. Based on the losses experienced by consumers due to damaged pawned goods, the parties must resolve the dispute. This research aims to determine the legal protection for customers as consumers for damage to collateral objects as well as to determine the resolution of disputes between the parties. The research method used in this writing uses normative juridical research methods. The author uses research methods with primary, secondary and tertiary legal materials. The data analysis method used by the author is a qualitative method, namely describing the research results from two variables, namely cause and effect by involving legal materials. The results of the research are in accordance with the problem formulation, namely that the pawnshop must take care of the collateral so that damage does not occur in accordance with existing regulations, legal protection for consumers can be given repressive legal protection, and dispute resolution can be carried out through mediation. It is hoped that suggestions regarding this problem will enable pawnshops to pay more attention to collateral items which are pledged as deposits, and to be able to care for collateral items properly to prevent damage which could result in losses for consumers.